Draft Genome Sequence of Rice Endophyte-Associated Isolate Kosakonia oryzae KO348 - Meng, Xianfa (Genome Announc, 2015)
Kosakonia oryzae KO348 is an endophytic and plant growth-promoting strain isolated from the roots of rice in Italy. Here, we report the draft genome sequence of Kosakonia oryzae KO348.